2007
DOI: 10.1159/000109986
|View full text |Cite
|
Sign up to set email alerts
|

Acute Corneal Epithelial Change after Instillation of Benzalkonium Chloride Evaluated Using a Newly Developed in vivo Corneal Transepithelial Electric Resistance Measurement Method

Abstract: Objective: Acute corneal permeability change after instillation of benzalkonium chloride (BAC) was evaluated using a newly developed in vivo corneal transepithelial electric resistance (TER) measurement method. Method: Corneal TER was measured by Ag/AgCl electrodes placed in the anterior aqueous chamber and on the cornea of live rabbit eyes. TER was measured and TER change after instillation of 0.05% BAC solution was monitored. After TER measurement, cornea was excised and fixed for transmission and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 46 publications
2
62
0
1
Order By: Relevance
“…In addition, TER was monitored with a recorder, which shows TER changes continuously. To our knowledge, no other study has evaluated acute corneal change within few second in vivo (Uematsu et al, 2007). However, the invasiveness of that procedure by inserting one electrode inside the anterior chamber makes it impossible for being used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, TER was monitored with a recorder, which shows TER changes continuously. To our knowledge, no other study has evaluated acute corneal change within few second in vivo (Uematsu et al, 2007). However, the invasiveness of that procedure by inserting one electrode inside the anterior chamber makes it impossible for being used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome that problem, in this study we recently developed a less invasive corneal TER measurement method. In previous studies, we demonstrated that benzalkonium chloride (BAC) concentrations between 0.005% and 0.02% immediately caused acute corneal barrier dysfunction (Kusano et al, 2010: Uematsu et al, 2007. So, our aim in this study is to evaluate acute corneal permeability change after instillation of BAC using a newly developed in vivo less invasive corneal TER measurement method in rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test methods in vivo , ex vivo and in vitro have been developed to predict eye irritation (Yamaguchi et al ., 2013). Concerning eye irritation tests (EITs) in vivo , the Draize rabbit EIT has been mainly utilized for evaluating cosmetic ingredients (Draize et al ., 1944; OECD, 2012a) and pharmaceutical agents (Uematsu et al ., 2007). Regarding those ex vivo , excised bovine corneas and chicken eyes successfully contributed to the establishment of Organisation for Economic Co‐operation and Development (OECD) Test Guidelines as the bovine corneal opacity permeability test (OECD, 2013) and isolated chicken eye test (OECD, 2009), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the scaffold was fabricated on a polyethylene terephthalate (PET) membrane of a Millicell chamber appropriate for the transepithelial electrical resistance (TEER) assay of epithelial cells. TEER is known as a suitable method for evaluating the integrity of the tight junction of corneal epithelium in vivo (Uematsu et al ., 2007). We examined four chemicals using the HCE model, and consequently demonstrated that the time‐dependent relative changes of TEER are useful indicators to assess ocular irritancy effects of chemicals even in the middle category (Takezawa et al ., 2011a).…”
Section: Introductionmentioning
confidence: 99%